Stakeholders' roles and policy effectiveness in organic rice farming development in Central Java and Yogyakarta, Indonesia - ROZAKI, ZUHUD; VIONANDA, REZA; RAHMAWATI, NUR; TRIYONO, TRIYONO (Asian Journal of Agriculture, 2025)
Abstract. Rozaki Z, Vionanda R, Rahmawati N, Triyono. 2025. Stakeholders' roles and policy effectiveness in organic rice farming development in Central Java and Yogyakarta, Indonesia. Asian J Agric 9: 513-521. In Central Java and Yogyakarta, organic rice farming has grown rapidly in response to increasing consumer demand and farmer awareness of environmental and health concerns. Between 2019 and 2022, the volume of organic rice trade rose significantly from 491.4 tons to 7,795.9 tons, highlighting the urgent need for supportive policies and governance structures. This study aims to analyze the roles of key stakeholders and assess the effectiveness of agricultural policies in promoting organic rice farming across five districts. A qualitative descriptive approach was applied, using purposive sampling to select 18 key informants, including officials from agricultural offices, extension advisors, and farmer group leaders. The findings show that stakeholders play a central and invaluable role in policy creation and information dissemination, yet marketing-related policies remain underdeveloped. Existing programs mainly provide production-side support, including subsidies for inputs, certification assistance, training, and extension services, all confirmed by farmers as received. While these interventions effectively enhance productivity, they have a limited impact on marketing efficiency. Further analysis highlights the need for stronger communication between policymakers and farmer groups, as well as better support for market access and post-harvest handling. The study recommends establishing district-level organic marketing boards, embedding farmer feedback into policy cycles, and encouraging local governments to adopt region-specific regulations that foster sustainable organic farming systems.